2019
DOI: 10.4048/jbc.2019.22.e2
|View full text |Cite
|
Sign up to set email alerts
|

Durable Response of Androgen Receptor-Positive Male Breast Cancer to Goserelin

Abstract: The luteinizing hormone-releasing hormone/androgen receptor (LHRH/AR) pathway is a promising treatment target in a subgroup of female patients with triple-negative breast cancer (TNBC). However, very little is known about the efficacy of this strategy in male patients with TNBC. In this report, we describe a male patient with AR-positive TNBC who was successfully treated using an LHRH agonist after pretreatment with several lines of chemotherapy and achieved a durable response. We also review the existing evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Notably, the AR expression rate in the current patient was >80% Figure 1C ), suggesting high dependence on AR signaling pathways for tumor survival and proliferation. One previous case report suggested a durable response of AR-positive male TNBC to goserelin ( 19 ), while another suggested a complete response of metastatic LAR TNBC to bicalutamide in a female patient ( 20 ). Notably, the AR expression rates in both these patients were 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the AR expression rate in the current patient was >80% Figure 1C ), suggesting high dependence on AR signaling pathways for tumor survival and proliferation. One previous case report suggested a durable response of AR-positive male TNBC to goserelin ( 19 ), while another suggested a complete response of metastatic LAR TNBC to bicalutamide in a female patient ( 20 ). Notably, the AR expression rates in both these patients were 100%.…”
Section: Discussionmentioning
confidence: 99%
“…There is however scant evidence of use of goserelin in MBC cases. Abdel Azim et al reported a 56-year-old male with bone metastases who achieved a year-long remission with goserelin monotherapy albeit with side-effects including grade II hot flushes and sexual dysfunction ( 14 ). Di Lauro et al treated 36 men with metastatic breast cancer using cyproterone acetate with or without goserelin ( 15 ).…”
mentioning
confidence: 99%